2014
DOI: 10.1111/jopr.12191
|View full text |Cite
|
Sign up to set email alerts
|

Flexural Properties of Poly(Methyl Methacrylate) Resin Reinforced with Oil Palm Empty Fruit Bunch Fibers: A Preliminary Finding

Abstract: Natural OPEFB fibers, especially OPEFB in cellulose form, can be considered a viable alternative to existing commercially available synthetic fiber reinforced PMMA resin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…OPEFB significantly increased the flexural strength and flexural modulus of acrylic resin. 23 Short ramie fiber also increased the flexural modulus of acrylic resin compared with conventional PMMA, but its flexural strength decreased as a result of weak interfacial bonding. The drawback of this fiber was its presentation in a long form, which requires extra work, ie, cutting and preparation.…”
Section: Natural Fibersmentioning
confidence: 99%
“…OPEFB significantly increased the flexural strength and flexural modulus of acrylic resin. 23 Short ramie fiber also increased the flexural modulus of acrylic resin compared with conventional PMMA, but its flexural strength decreased as a result of weak interfacial bonding. The drawback of this fiber was its presentation in a long form, which requires extra work, ie, cutting and preparation.…”
Section: Natural Fibersmentioning
confidence: 99%
“…Some of the shortcomings of incorporating conventional long or short fibers into denture base polymer mixture would include lack of bonding between the fiber particle and the powder/liquid mixture producing voids, 35 fraying of the margins of the poly-merized specimens noticed during polishing of the specimens, which often occurs due to exposure of the fibers. 36 In this study, however, contrary to the common challenges of placing reinforcement fibers, 16,37 the authors found that MCC was easily and homogeneously added and mixed with the PMMA, and there was no fear of fiber projection in the case of degradation, displacement during processing, or fracture. This shows that the cellulose is evenly distributed in the resin matrix, and the level of impregnation of the MCC with the polymer framework was extremely good.…”
Section: Discussionmentioning
confidence: 62%
“…They are from renewable resources, considered free of biohazards, and more cost-effective when compared to synthetic fibers; however, mucosal irritation and patient discomfort due to the direct use of long or short fibers in the denture base can lead to clinical problems. 15 One recent study 16 concluded that oil palm empty fruit bunch (OPEFB) in its microcrystalline cellulose (MCC) form can be considered as a viable alternative to existing commercially available synthetic fiber-reinforced denture base resins. MCC is a biodegradable, purified, white, odorless, fine, non-fibrous, and partially depolymerized crystalline powder, usually isolated from cellulose through the hydrolysis process.…”
mentioning
confidence: 99%
“…ideally FPD (fixed partial denture) base material should have superior surface texture and mechanical properties. in 1936 Walter Wright introduced acrylic resin material called polymethylmethacrylate (PMMA) to the market (Keyf, uzun and Mutlu, 2003;Baba, 2016). This material became one of the most popularly used denture base materials due to its ease of handling and manipulation of the material, it is less toxic, has good aesthetic results, shows adequate strength, easily repaired, the stability in the oral cavity was better when compared with other materials, low solubility, reasonable cost, and low water absorption (Kim and Watts, 2004).…”
Section: Introductionmentioning
confidence: 99%